2019
DOI: 10.1002/mbo3.952
|View full text |Cite
|
Sign up to set email alerts
|

Acetylome analysis of lysine acetylation in the plant pathogenic bacterium Brenneria nigrifluens

Abstract: Brenneria nigrifluens (synonym: Erwinia nigrifluens) (Hauben et al., 1998) is the pathogen of walnut trees with shallow bark canker.The disease and its causal agent were first described in California (USA) (Wilson, Stake, & Berger, 1957). Then, the shallow bark cankers of walnut trees caused by B. nigrifluens were identified in Spain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
1
6
1
Order By: Relevance
“…Of the 1,924 acetylated proteins, 65.80% contain two or more acetylation sites, and 4.47% contain more than 10 acetylation sites ( Figure 4B ). This proportion is also slightly higher than that found in previous studies ( Jers et al, 2017 ; Li et al, 2020 ; Pang et al, 2020 ), while further experiments are required to validate these acetylated proteins in the future. We further determined the frequencies of amino acids around the acetylated lysine site ( Supplementary Table S6 and Supplementary Figure S6 ).…”
Section: Resultscontrasting
confidence: 62%
See 1 more Smart Citation
“…Of the 1,924 acetylated proteins, 65.80% contain two or more acetylation sites, and 4.47% contain more than 10 acetylation sites ( Figure 4B ). This proportion is also slightly higher than that found in previous studies ( Jers et al, 2017 ; Li et al, 2020 ; Pang et al, 2020 ), while further experiments are required to validate these acetylated proteins in the future. We further determined the frequencies of amino acids around the acetylated lysine site ( Supplementary Table S6 and Supplementary Figure S6 ).…”
Section: Resultscontrasting
confidence: 62%
“…found in previous studies (Jers et al, 2017;Li et al, 2020;Pang et al, 2020), while further experiments are required to validate these acetylated proteins in the future. We further determined the frequencies of amino acids around the acetylated lysine site ( Supplementary Table S6 and Supplementary Figure S6).…”
Section: Comprehensive Analysis Of Lysine Acetylated Proteins In V Vmentioning
confidence: 64%
“…Motif K ac R has been reported in other species of bacteria and plants, such as Streptococcus pneumoniae , Vibrio cholerae , Cyanobacterium Synechocystis sp., wheat ( Triticum aestivum L.), and Zea mays ( Mo et al, 2015 ; Carsten et al, 2017 ; Liu et al, 2018 ; Guo et al, 2020 ; Yan et al, 2020 ), indicating that the K ac R motif is conserved and widespread. Motif K ac L and L.K ac have been reported in Brenneria nigrifluens ( Li Y. et al, 2020 ). The other motifs, LK ac K, L(-7) EK ac K, and IEK ac , are rarely identified in other bacteria.…”
Section: Resultsmentioning
confidence: 94%
“…The discovery here that acetylation of one specific lysine residue in FolSvp1 increases the stability of this protein in Fol and in planta, promoting invasion of tomato, provides a clear example of a direct effect of acetylation on a biological process in plant pathogens. With the recent discovery that a large number of putative effectors are acetylated in fungi ( Li et al, 2020a , Lv et al, 2016 ; Zhou et al, 2016 ), Phytophthora ( Li et al, 2016 ), and bacteria ( Li et al, 2020b , Ren et al, 2017 ), it is likely that the findings reported here are only the beginning of what will be a widespread phenomenon in plant pathogens.…”
Section: Discussionmentioning
confidence: 94%